Kedwibahasaan pada Siswa SMP dan Dampaknya terhadap Proses Belajar Bahasa Indonesia - Fitri Yani Salsabila Ritonga; Sandifa Anggraini; Syahrul Syahrul; Elfia Sukma; Norliza Binti Jamaluddin (STIKes Ibnu Sina Ajibarang, 2025)
Bilingualism of Junior High School Children and Its Implications for Indonesian Language Learning. This research seeks to explore how much interaction takes place between a child’s native language and their second language in junior high school students. The phenomenon of using multiple languages (bilingualism) is observed not just in informal settings, but it also extends into formal environments. This practice leads to children experiencing difficulties in differentiating between languages.